Effect of Thermal Hydrolysis Pretreatment on Anaerobic Digestion of Protein-Rich Biowaste: Process Performance and Microbial Community Structures Shift - Shi, Jingyang; Zhang, Guangyi; Zhang, Hang; Qiao, Fa; Fan, Jie; Bai, Dingrong; Xu, Guangwen (Frontiers in Environmental Science, 2022)
To reveal effects of thermal hydrolysis (TH) pretreatment (THPT) on anaerobic digestion (AD) of protein-rich substrates, discarded tofu was chosen as the object, and its batch AD tests of tofu before and after being subjected to TH at gradually increasing organic loads were carried out and the AD process characteristics compared; further, its continuous AD tests without and with THPT were also conducted and the difference of the microbial community structures was investigated. The results showed that, during AD of protein-rich tofu with increase in the organic load there appeared the inhibition from severe acidification prior to accumulation of ammonia nitrogen (AN). THPT helped overcome the acidification inhibition present in batch AD of tofu at such a high TS content as 3.6%, to obtain the maximum methane yield rate of 589.39 mL·(gVS)-1. Continuous AD of protein-rich tofu heavily depended on ammonia-tolerant hydrogenotrophic methanogens and bacteria. The continuous AD processes acclimated by HT substrates seemed to be resistant to severe organic loads, by boosting growth of ammonia-tolerant microorganisms, above all methylotrophic methanogens such as the genera RumEnM2 and methanomassiliicoccus. The process response of continuous AD of HT tofu was hysteretic, suggesting that a sufficiently long adaptation period was required for stabilizing the AD system.